International Entrepreneurship: Thematic Mapping and Research Agenda Proposal - Andrés Ortiz-Rojo, Ramón; José Lacruz, Adonai (Organizações & Sociedade, 2023)
This study aimed to carry out a bibliometric analysis of the production on International Entrepreneurship IE based on perspectives of the thematic structure of the field using thematic mapping techniques to model the knowledge produced in it. Data from the scientific production on the subject were collected from Scopus and Web of Science databases. Three thematic maps representing the periods of 1995-2004, 2005-2014 and 2015-2022 were yielded in the study. The discussion of results concludes that IE is a research area that has grown significantly since the second period, showing a considerable increase in publications from 127 in the first period to 1,042 in the second. This increase remained constant reaching 1,934 in the third and final period. The themes that stood out the most and were most representative in the field of IE were: performance of companies in IE, innovation, knowledge, entrepreneurial companies, entrepreneurial orientation, management, strategy, model and export behavior. A conceptual variation of the themes was also observed with the performance theme standing out, maintaining a high representativeness in the three periods analyzed with displacements between the basic themes – transversal – and the driving themes. Another highlight was the capabilities theme, which, over time, resulted in the dynamic capabilities theme. As emerging themes, performance, entrepreneurial orientation, entrepreneurship, impact and management appear. Based on the results and conclusions of this study, a research agenda is proposed.